COMPARATIVE STUDY OF EFFICACY AND SAFETY OF AZITHROMYCIN ALONE AND IN COMBINATION WITH PROBIOTIC IN THE TREATMENT OF IMPETIGO IN CHILDREN - Sudha G., Dharani; P., Nirmala; R., Ramanathan; Samuel, Vanitha (International Journal of Current Pharmaceutical Research, 2017)
Objective: Impetigo is a superficial infection of the skin that involves only the epidermis. It affects mostly children, usually on exposed areas of the body (eg. The face and the legs). Staphylococcus aureus is the most important causative organism. Streptococcus pyogenes (i.e.) group A beta-hemolytic streptococcus) causes fewer cases, either alone or in combination with S. aureus. The objective of this study is to find out the efficacy and safety of azithromycin alone and in combination with probiotic among children suffering from impetigo. Methods: This prospective, randomized, single-blinded interventional study was conducted for a period of 6 mo in pediatric OPD and dermatology OPD in Rajah Muthiah Medical College and Hospital. A total of 100 patients, randomly divided into two groups with 50 patients in each group. Group, I patients treated with Azithromycin 10 mg/kg/d for 5 d. Group II patients treated with Azithromycin 10 mg/kg/d for 5 d with probiotic (50 million spores of Lactobacillus sporegens, Streptococcus faecalis 30 million spores, clostridium butyricum 2 million spores, Bacillus mesentericus 1 million spores) twice daily for 5ds. Results: Reduction in a number of lesions and wound area, clinical response were highly significant in Azithromycin with the probiotic-treated group. Conclusion: In this study, probiotic bacteria may counteract the inflammatory process beyond the intestinal milieu. The results of this study indicate that Azithromycin with probiotic is effective in the treatment of impetigo.